A critical overview of the current myofascial pain literature – June 2017. Issue 3 (July 2017) - Dommerholt, Jan; Chou, Li-Wei; Finnegan, Michelle; Hooks, Todd
Abstract: We would like to welcome Dr. Li-Wei Chou, MD, PhD as our newly appointed contributing author. Dr. Chou is Assistant Professor at China Medical University in Taichung, Taiwan and he has an impressive publication record with many research studies and book chapters. The current overview includes several articles comparing dry needling (DN) to acupuncture with sharply contrasting points of view. Several basic studies shed further light on the nature of myofascial pain, myalgia, fascia and examination techniques, such as sonoelastography. Neuroimaging studies demonstrated microstructural abnormalities in brain gray matter of chronic myofascial pain patients, which is an important new finding. As usual, many manual TrP papers and DN papers were published in the past several months.